2020
DOI: 10.1155/2020/4861719
|View full text |Cite
|
Sign up to set email alerts
|

Pulchinenosides from Pulsatilla Chinensis Increase P‐Glycoprotein Activity and Induce P‐Glycoprotein Expression

Abstract: Five pulchinenosides (pulchinenoside B3, pulchinenoside BD, pulchinenoside B7, pulchinenoside B10, and pulchinenoside B11) isolated from Pulsatilla chinensis (Bge) Regel saponins extract exhibited strong antitumor activities but poor gastrointestinal absorption properties. The enteric induction of P-glycoprotein (P-gp) is understood to restrict the oral bioavailability of some pharmaceutical compounds and lead to adverse drug reactions. Therefore, the present investigation was intended to delineate the impacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Although these studies have already been proven effec- polyacetylenes (Srivalli & Lakshmi, 2012;Abdallah et al, 2015;Zhou et al, 2004;Junco et al, 2013;Yu et al, 2016;Dewanjee et al, 2017;Peng et al, 2020). Pulchinenosides induced the P-gp and stimulated the ATP-dependent transport of N-methyl-quinidine (Liu et al, 2020).…”
Section: Natural P-gp Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these studies have already been proven effec- polyacetylenes (Srivalli & Lakshmi, 2012;Abdallah et al, 2015;Zhou et al, 2004;Junco et al, 2013;Yu et al, 2016;Dewanjee et al, 2017;Peng et al, 2020). Pulchinenosides induced the P-gp and stimulated the ATP-dependent transport of N-methyl-quinidine (Liu et al, 2020).…”
Section: Natural P-gp Inhibitorsmentioning
confidence: 99%
“…However, several reports concerning the activity of various plant extracts and their constituents as P‐gp inhibitors; viz., anthraquinones, phenylbutanoids, phytosterols, cannabinoids, carotenoids, curcuminoids, volatile oils, sulfur compounds, and polyacetylenes (Srivalli & Lakshmi, 2012; Abdallah et al, 2015; Zhou et al, 2004; Junco et al, 2013; Yu et al, 2016; Dewanjee et al, 2017; Peng et al, 2020). Pulchinenosides induced the P‐gp and stimulated the ATP‐dependent transport of N‐methyl‐quinidine (Liu et al, 2020). Wutou‐Gancao herb and liquorice bioactive ingredients (liquiritigenin) enhanced the Cmax and AUC of Aconitine by inhibiting P‐gp (He et al, 2020).…”
Section: Approaches To Overcome the Effects Of P‐gpmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been used to treat bacillary dysentery for thousands of years. Modern studies have shown that it has anti‐inflammatory, antibacterial, antioxidant, antitumor, and other pharmacological effects [1–15], leading to its application in proprietary Chinese medicine. Triterpenoid saponins were predominant biologically active constituents, and these were subcategorized into lupane and oleanane saponins on skeletal basis [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been used to treat bacillary dysentery for thousands of years. Modern studies have shown that it has anti-inflammatory, Article Related Abbreviations: EMRT, exact mass retention time; OPLS-DA, orthogonal partial least square discriminant analysis; PCA, principal component analysis; RT, retention time antibacterial, antioxidant, antitumor, and other pharmacological effects [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], leading to its application in proprietary Chinese medicine. Triterpenoid saponins were predominant biologically active constituents, and these were subcategorized into lupane and oleanane saponins on skeletal basis [16,17].…”
Section: Introductionmentioning
confidence: 99%